PERBANDINGAN MOTIVASI BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR DENGAN MODEL PEMBELAJARAN DISCOVERY LEARNING DAN ACCELERATED LEARNING PADA MATERI INTEGRAL DI MAN 4 MARTUBUNG - Winda Suci Lestari Nasution (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the differences in the use of the Discovery Learning learning model and the Accelerated Learning learning model on the learning outcomes of highly motivated students, the differences in the use of the Discovery Learning learning model and the Accelerated Learning learning model on the learning outcomes of students who have low motivation, the difference in the use of the Discovery Learning model. Learning on the learning outcomes of students who have high and low motivation, the difference in the use of Accelerated Learning learning models on learning outcomes of students who have high and low motivation. This research is a quantitative research with a quasi-experimental research type. The population is all students of class XI MAN 4 Medan in the 2019/2020 academic year, which consists of 4 classes, while the 2 class samples are class XI IPA-1 and XI IPA-2, totaling 30 people in each class. Data analysis was performed using regression analysis. The instruments used were tests and questionnaires. The results of these findings indicate: 1) The mathematics learning outcomes of students who have high motivation are taught with the Discovery Learning learning model better; 2) The mathematics learning outcomes of students who have low motivation are taught using the Discovery Learning learning model better; 3) The learning outcomes of students who have the low motivation is taught with the Discovery Learning learning model better; 4). Mathematics learning outcomes of students who have high motivation are taught with the Accelerated Learning model better